Managing Character Education for Students with Special Needs: A Framework of Planning, Organizing, Implementation and Evaluation - Mala, Rohmanur; Surya, Priadi; Tarso; Soswanto, Deny Hadi (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This study explores the implementation of character education at SD Muhammadiyah Pulokadang for students with Special Educational Needs (SEN). Using a qualitative case study design, this analysis examines how character education is planned, organized, implemented, and evaluated within an inclusive elementary school setting. Data were gathered through direct observation, semi-structured interviews with school leaders and teachers, and analysis of school documents. Thematic analysis revealed that the school incorporates 18-character values, adapted to the local context, into all learning modules and daily routines. Character education is carried out through modelling, habituation, and reinforcement, supported by a dual-homeroom teacher model and differentiated instruction across regular, intensive, and transitional classes. Regular evaluations, aligned with continuous improvement principles, help monitor students’ character development and inform program refinement. The findings highlight how inclusive management strategies and adaptation to local contexts can effectively support character education for SEN students. This framework offers practical insights that may be replicated or adapted by other inclusive schools aiming to strengthen character education.